METODE PENILAIAN HADIS DALAM TRADISI SYI’AH IMAMIYAH DAN APLIKASINYA - Nursalim, Danni; Masrur, Ali; Arifin, Tajul (Andragogia: Journal Education Science And Islamic Studies, 2026)
Shi'a Imamiyah is the second largest Islamic religious sect in the world that still exists today. This sect has a sizable treasure of Islamic sciences that demonstrate their existence as well as to strengthen the foundations of their beliefs that are different from the Sunnis. One of the disciplines that they pursue is the science of hadith, which although somewhat late in its development compared to the sunnis. This study aims to reveal the differences between the methods of hadith evaluation in the Shi'a Imamiyah tradition and those used by the Sunnis. This research uses qualitative method by collecting data through (library search) technique. The results show that there are similarities in the terms used by the Shi'a Imamiyah and the Sunnis in the method of assessing hadith, but there are fundamental differences in its definitions and in its applications.